"Chaplains for Wellbeing" in Primary Care: A Qualitative Investigation of Their Perceived Impact for Patients' Health and Wellbeing. Issue 4 (1st October 2016) - McSherry, Wilfred; Boughey, Adam; Kevern, Peter
Abstract : Although Health Chaplaincy services are well-established in hospitals in the United Kingdom and across the world, Primary Care Chaplaincy is still in its infancy and much less extensively developed. This study explored the impact the introduction of a Primary Care "Chaplains for Wellbeing" service had upon patients' experience and perceived health and well-being. Sixteen patients participated in one-one interviews. Transcripts were analyzed using interpretative phenomenological analysis (IPA). Patients reported circumstances that had eroded perceived self-efficacy, self-identity, and security manifesting as existential displacement; summarized under the superordinate theme of "loss." "Loss" originated from a number of sources and was expressed as the loss of hope, self-confidence, self-efficacy, and sense of purpose and meaning. Chaplains used a wide range of strategies enabling patients to rebuild self-confidence and self-esteem. Person-centered, dignified, and responsive care offered in a supportive environment enabled patients to adapt and cope with existential displacement.